Bilateral Morgagni hernia: operative discovery of appendix lying on superior pulmonary vein. Issue 3 (August 2013) - Lammy, S; Stewart, M; Carnochan, FM; Walker, WS
A patient presented having an acute abdomen on a background of a twelve-month history of worsening asthma. Computed tomography showed giant bilateral intrathoracic hernias extending to both thoracic apices. Our case was unusual as the defect was bilateral and left-sided. Surgical repair revealed each hernia sac measuring >20 cm and to contain the entirety of the small bowel and colon (including retroperitoneal bowel). The appendix was discovered adjacent to right superior pulmonary vein. Both sacs were excised and the defects dissected and transfixed in a single stage operation. In the post-operative stage, he developed a 6.3 cm fluid collection anterior to the right atrium and a left-sided pleural effusion. Morgagni hernias can escape detection and be attributed to other diagnoses courtesy of false localising signs on clinical examination and symptoms in the history.